Phenotypic evaluation of a multi-location cassava breeding trial to improve a genomic selection training population - Uchendu, U.K.; Parkes, Elizabeth Y.; Aina, O.O.; Akoroda, M.O.; Kulakow, Peter A. (International Association of Hydrological Sciences, 2013)
Thirty white fleshed cassava genotypes derived from crosses between genotypes from West Africa x East Africa and West Africa x Latin America were evaluated in five major agroecological zones in Nigeria during 2012-2013. The trials were established in a randomized complete block design with four replications. The objectives of the study were (i) to evaluate genotype (G), environment (E), and G X E interaction on cassava mosaic disease (CMD), cassava bacterial blight (CBB), cassava anthracnose disease (CAD), and cassava green spider mite (CGM) in a multi-location uniform yield trial and (ii) to characterize morphological variation to improve a genomic selection training population that includes these genotypes. Combined analysis of variance showed differences (P-<- 0.001) among E for all traits evaluated. Genotypes did not differ significantly in their field reaction to CMD and CBB but showed variation in mild CAD symptoms and more severe, CGM reaction. Environmental variation accounted for 53.09% of the total sum of squares for CMD; 49.53% for CBB; 64.76% for CAD and 59.39% for CGM. The high influence of E demonstrated large differences in disease and pest severity in different locations. Morphological parameters such as levels of branching, angle of branching, height of branching, and plant height varied significantly among genotypes. Genotypes I090488, I090536 and I090590 branched the most, while I090574, I090564 and TMEB 419 (check) branched the least. Our results revealed that genotypes I090506, I090537 and I090609 were either low branching or have a wide angle of branching. This is significant as it helps in suppressing the weed flora, especially spear grass (Imperata cylindrical) by forming a dense canopy.